2005
DOI: 10.1111/j.1439-0388.2005.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of the F4ab, F4ac and F4ad E. coli receptors in swine and examination of four candidate genes for F4acR

Abstract: Susceptibility to enterotoxigenic Escherichia coli with fimbriae F4ac is dominantly inherited in the pig. A three-generation pedigree was created to refine the position of F4acR on chromosome 13 comprising 202 pigs: eight parents, 18 F1 and 176 F2 pigs. The 17-point analysis indicates that F4acR lies between Sw207 and S0283. Recombinant offspring specify that the most probable order is Sw207-S0075-F4acR-Sw225-S0283. We observed six phenotypes for the three fimbrial variants F4ab, F4ac and F4ad. The two missing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 26 publications
4
48
0
1
Order By: Relevance
“…To test this hypothesis we performed repetitive and targeted matings in which the same pig was mated to different phenotypes (Table 6), for example, sire 2674 was mated to four different resistant dams and sire 2831 was mated to five different dams which were resistant, FA or PA. Dam 2842 was mated to R and FA sires. Although we increased the number of intestinal sites for the adhesion test to four compared with only one site used in previous studies (Python et al, 2002 and2005) it cannot be excluded that we mistyped PA pigs by chance as resistant pigs. A separate χ 2 was calculated in litters with expected FA phenotype to test the two gene inheritance model for the FA receptor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To test this hypothesis we performed repetitive and targeted matings in which the same pig was mated to different phenotypes (Table 6), for example, sire 2674 was mated to four different resistant dams and sire 2831 was mated to five different dams which were resistant, FA or PA. Dam 2842 was mated to R and FA sires. Although we increased the number of intestinal sites for the adhesion test to four compared with only one site used in previous studies (Python et al, 2002 and2005) it cannot be excluded that we mistyped PA pigs by chance as resistant pigs. A separate χ 2 was calculated in litters with expected FA phenotype to test the two gene inheritance model for the FA receptor.…”
Section: Discussionmentioning
confidence: 99%
“…A (Python et al, 2005;Yan et al, 2009;Schroyen et al, 2012). Ren et al (2012) showed evidence that MUC13 is a good candidate for the F4ac receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Susceptibility to E. coli K88ab/ac has been firmly established as a dominant monogenetic trait (Python et al, 2005). In this study, F41 adhesion phenotypes were recorded only for F 2 animals.…”
Section: Qtl Detectionmentioning
confidence: 96%